Spiegare gentilmente i passaggi e il ragionamento.
dal grafico deduciamo che l'area A vale
$ A = \int_{-2}^{-1} -\frac{1}{2} (x^3-3x^2+4) \, dx + \int_{-1}^2 \frac{1}{2} (x^3-3x^2+4) \, dx $
$ A = \frac{1}{2} [\int_{-2}^{-1} -(x^3-3x^2+4) \, dx + \int_{-1}^2 (x^3-3x^2+4) \, dx] $
$ A = \frac{1}{2}[ \left. -\frac{x^4}{4} +x^3 -4x\right|_{-2}^{-1} + \left. \frac{x^4}{4} -x^3 +4x\right|_{-1}^2] $
$ A = \frac{1}{2}[ \frac{11}{4} + 4 + 4 + \frac{11}{4}] $
$ A = \frac{11}{4} + 4 $
$ A = \frac{27}{4} $